Design Of Sensory Park As Educational Park For Children With Special Needs At Autism Service Center, Denpasar City - Made Anggita Wahyudi Linggasani; Ni Made Widya Pratiwi; Putu Nugrahaeni Widiasavitri (Fakultas Teknik Universitas Warmadewa, 2021)
Autism is defined as a special behavior that affects a person in communicating or interacting with other people or certain objects. There are varying degrees of autism, but some of the common behaviors associated with this disability include poor motor skills, speech delays, difficulties with skills such as reasoning, and very narrow interests. The Growth and Development Group for Children with Special Needs is an educational service for children with special needs in Denpasar City. Currently, almost all facilities are available in PLA, but outdoor facilities in the form of sensory gardens are not yet available. Therefore, partners want to provide a sensory garden to meet the educational needs of children with special needs and until now it is still difficult to find expertise to design this special garden. There are several problems that are summarized related to the procurement of this sensory park, namely the limitations of available land, the ideal sensory garden design and calculation of the estimated cost of sensory garden realization. By using the design method and approach to the needs of children with special needs, psychological aspects and sensory sensitivity are the main things in the preparation of this sensory garden design. Seeing these obstacles, it is necessary to design an ideal sensory garden, because PLA wants to realize this park and get funding from the government for the sustainability and educational needs of students with special needs.